Syringotropic Lichen Planus: An Unusual Presentation of a Common Dermatosis - A Report of 2 Cases - Fatemeh Mohaghegh; Zohre Khodashenas; Mina Saber; Haniyeh Sohrabi (Karger Publishers, 2024)
Introduction: Lichen planus (LP) is a chronic inflammatory dermatosis that causes plaques and itchy papules on the skin, as well as erosion and ulcers in the mucous membranes. LP is characterized by a dense dermal T-cell infiltration. Perieccrine inflammation can be seen in a variety of dermatoses, but genuine lymphocyte permeation of the secretory coil or lymphocytic syringotropism is a rare sign that is typically seen in mycosis fungoides. Case Presentation: In this study, we present 2 uncommon instances of lymphocytic syringotropism in LP. Histopathological examination revealed dense T-cell infiltration and lymphocytic involvement of eccrine glands, confirming syringotropism. Conclusion: Lymphocytic syringotropism is an uncommon finding in LP. Its presence broadens the histopathological spectrum of LP and highlights the need to differentiate it from lymphoproliferative disorders like mycosis fungoides.